Existência e imanência: eternidade e duração na ética de Spinoza - Pacheco, Gionatan Carlos (2023)
This thesis is an interpretation of the existential notions of Spinoza’s Ethics. Its main objective is to clarify both the distinction between the concepts of duration and eternity, as well as their unity in the concept of existence. With that, its responds to a very persistent discussion in relation to the texts that culminate the Ethics, which supposedly contain a problematic “doctrine of the mind’s eternity”. Its reading key is to take the immanence relationship between the substance and the modes as a gauge of intelligibility of the unit and distinction between eternity and duration. The immanence between mode (or singular) and substance implies both the relation of each singular to the substance, a relation of belonging in which we understand the eternity of the singular, and the relations of singulars to each other, a relation of existential tension characterized by duration. In this key, then, mode and substance are for being, just as duration and eternity are for existence, the unity and distinction of being between substance and its modifications explains to us the existential unity and distinction between duration and eternity. This text is composed of different moments: first, it deals with the basic notions for understanding Spinoza’s immanence, that is, the intelligibility gauge we use to present our understanding of the concepts of duration and eternity and, then, answer the problems that we highlight as main and most persistent in relation to the specialized literature. From these steps, we conclude that: eternity and duration are the same existence, they are not reduced to ways of perceiving existence and are irreducible to each other; the definition of eternity is the same throughout the entire Ethics; there is not properly a “doctrine of the mind’s eternity” in the texts that close this work; these texts are organic and consistent with the antecedents; the “eternal part of the mind” has the function of comparing the mind of the wise and that of the ignorant. In the rest of the text, we first demonstrate the insufficiency of what we call the “temporal fork”, which restricts the meaning of eternity to two senses subordinated to the notion of time, both in Spinoza and in relation to the philosophical tradition in general. Next, we review the studies and discussions on the texts that close the Ethics, in chronological order: we start with the 19th20th century, in which we briefly address the problems of reception of Spinoza’s work and in which the focus is the question of the personhood of the mind’s eternity; then, we problematize the readings of the concept of eternity as “property”, and advance to the most recent comments, through which we diagnose a crisis of what we call the “temporal fork”, as well as problematize the recent speculations about Spinoza’s concept of essence.